PBX1 promotes development of natural killer cells by binding directly to the Nfil3 promoter. Issue 5 (19th March 2020) - Xu, Xiuxiu; Zhou, Yonggang; Fu, Binqing; Zhang, Jinghe; Dong, Zhongjun; Zhang, Xiaoren; Shen, Nan; Sun, Rui; Tian, Zhigang; Wei, Haiming
Abstract: The transcription factor nuclear factor interleukin‐3‐regulated protein (NFIL3, also called E4BP4) is crucial for commitment of natural killer (NK) cells from common lymphoid progenitors (CLPs). However, the identity of the factor that can regulate NFIL3 directly during the NK‐cell development is not known. Here, we reveal that pre‐B‐cell leukemia transcription factor 1 (PBX1) can upregulate the NFIL3 expression directly. We used conditional knockout mice in which PBX1 in hematopoietic cells was specifically absent. The number of NK‐committed progenitor pre‐NKP cells and rNKP cells was reduced significantly in the absence of PBX1, which was consistent with NFIL3 deficiency. Also, the NFIL3 expression in NK cells was decreased if PBX1 was absent. We demonstrated that PBX1 was bound directly to the promoter of Nfil3 and facilitated transcription. Upon knockout of the binding site of PBX1 in the Nfil3 promoter, mice showed fewer NK‐precursor cells and NK cells, just like that observed in Nfil3  knockout mice. Furthermore, asparagine N286 in the homeodomain of PBX1 controlled the binding of PBX1 to the Nfil3 promoter. Collectively, these findings demonstrate that the transcription factor PBX1 promotes the early development of NK cells by upregulating the Nfil3 expression directly.